Transforming places : lessons from Appalachia - Fisher, Stephen L., 1944-; Smith, Barbara Ellen, 1951- (Urbana : University of Illinois Press, 2012)
"In this era of globalization's ruthless deracination, place attachments have become increasingly salient in collective mobilizations across the spectrum of politics. Like place-based activists in other resource-rich yet impoverished regions across the globe, Appalachians are contesting economic injustice, environmental degradation, and the anti-democratic power of elites. This collection of seventeen original essays by scholars and activists from a variety of backgrounds explores this wide range of oppositional politics, querying its successes, limitations, and impacts. The editors' critical introduction and conclusion integrate theories of place and space with analyses of organizations and events discussed by contributors. Transforming Places illuminates widely relevant lessons about building coalitions and movements with sufficient strength to challenge corporate-driven globalization."--Publisher's website
Stop the bombs: local organizing with global reach / Ralph Hutchison -- RAIL solution: taking on Halliburton on the home front / Rees Shearer -- This land is your land: local organizing and the hegemony of growth / Nina Gregg and Doug Gamble -- Identity matters: building an urban Appalachian movement in Cincinnati / Phillip J. Obermiller [and others] -- Appalachian youth re-envisioning home, re-making identities / Katie Richards-Schuster and Rebecca O'Doherty -- Resistance through community-based arts / Katie Maureen Mullinax -- Organizing Appalachian women: hope lies in the struggle / Meredith Dean with Edna Gulley and Linda McKinney -- The southern empowerment project: homegrown organizing gone too soon / Jane Rostan and Walter Davis -- Center for participatory change: cultivating grassrootssupport organizing / Craig White [and others] -- Faith-based coalitions and organized labor: new forms of collaboration in the twenty-first century? / Jill Kriesky and Daniel Swan -- Talking union in two languages: labor rights and immigrant workers in East Tennessee / Fran Ansley -- Virginia organizing: the action is at the state level / Joe Szakos and Ladelle McWhorter -- OxyContin flood in coal fields: "searching for higher ground" / Sue Ella Kobak -- Not your grandmother's agrarianism: The Community Farm Alliance's agrifood activism / Jenrose Fitzgerald, Lisa Markowitz, and Dwight B. Billings -- Mountain justice / Cassie Robinson-Pfleger [and others] -- Who knows? Who tells? Creating a knowledge commons / Anita Puckett [and others] -- North and South: struggles over coal in Colombia and Appalachia / Aviva Chomsky and Chad Montrie -- Conclusions: transformations in place / Barbara Ellen Smith and Stephen L. Fisher.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Community organization -- Appalachian Region; Social action -- Appalachian Region; Political participation -- Appalachian Region; Appalachian Region -- Social conditions; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; BUSINESS & ECONOMICS -- Economics -- Comparative; POLITICAL SCIENCE -- Economic Conditions; HISTORY -- Social History; Community organization; Political participation; Social action; Social conditions; Appalachian Region